Analisis Kepuasan Pelayanan Kesehatan pada Pasien Rawat Inap di RSUD Rupit Kabupaten Musi Rawas Utara Tahun 2026 - Tanti Nurhasanah; Arie Wahyudi; Chairil Zaman (JURNAL KESEHATAN TERAPAN, 2026)
This study aims to analyze the level of patient satisfaction with health care services at the Rupit Regional General Hospital in North Musi Rawas Regency in 2026. Patient satisfaction is a crucial indicator in evaluating the quality of health care services. This study employs a quantitative research design with a descriptive-analytical approach and a cross-sectional design. The study sample consisted of 106 respondents who were family members of adult inpatients. Data were collected through a structured questionnaire and analyzed using univariate, bivariate (Chi-Square test), and multivariate (multiple logistic regression). The results of there was a significant association between the dimensions of tangibles (p=0.005), responsiveness (p=0.001), assurance (p=0.001), Reliability (p=0.001), and empathy (p=0.001) and patient sati sfaction. Multivariate analysis identified assurance as the most dominant variable influencing patient satisfaction (OR = 3.523), followed by the tangible dimension (OR = 3.001) The resulting predictive model is Z = -0.929 + 1.099(Tangible) + 1.259(Assurance ), indicating a 28.3% probability of satisfaction for respondents who perceive both of these dimensions as “poor” simultaneously. In conclusion, patient satisfaction at Rupit Regional General Hospital is significantly influenced by the tangible and assurance dimensions. Hospital management is advised to prioritize improvements in the assurance and tangible dimensions through regular training for staff and upgrades to facilities and infrastructure to sustainably enhance patient satisfaction.